Sistem Pencarian Lokasi Hotel Berdasarkan Rute Terpendek Untuk Pengunjung Objek Wisata Alam Di Kota Medan Menggunakan Algoritma Dijkstra - Aulia Rizky Fadillah (STMIK Budi Darma, 2019)
Hotel location search system for visitors to natural attractions. The hotel is a haven for visitors who are traveling, tourists must look for a hotel that is closest to where the object they are visiting. Searching for hotels makes visitors need to determine the location of the hotel closest to the tourist object. In this study a hotel location search system was built based on the shortest route with the Dijkstra algorithm method. From several methods in accordance with the search for the shortest path is to use the Dijkstra method. Algorithm method is one algorithm that is effective in providing the shortest route from a location search Hotels for tourist visitors. Why choose the Dijksta Algorithm method because the Selection method is more optimal and easier to understand than the model